CHALLENGES AND OPPORTUNITIES IN APPROACH THERAPY OF RHEUMATOID ARTHRITIS - Ângela Sequeira Silva; Bruno Rosa; João Soares; Bruno Sepodes (Revista Portuguesa de Farmacoterapia, 2013)
Rheumatoid arthritis is a chronic inflammatory auto-immune disease characterized by a progressive destruction of joints and variable extra-articular manifestations. More prevalent among women, usually develops between 35 and 50 years, and there is a genetic predisposition. The etiology remains unknown but is consensus the importance of T lymphocytes, B lymphocytes and cytokines in the inflammatory process. It is important then to tackle the disease by a multi-disciplinary strand which includes symptoms control with the use of analgesics and anti-inflammatory drugs, and use of glucorticosteroids, disease-modifying drugs and new biological drugs aimed to control disease progression. It’s associated to the pharmacological approach complementary therapies, surgery and patient education programs. This review intended to raise awareness of the complexity of this disease and what the science has offered us, as new strategies pharmacological / non-pharmacological, always with the aim of contributing to an improved quality of life in patients with rheumatoid arthritis.